(3GJLGgGJ GdeSJgdcjf fMh OhdI GdefTC hCKQgG Ydi JUeje GdeRjL GdJShjbj (B/s - (3Ydj, gHI aDGOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2004)
(3GJLGgGJ GdeSJgdcjf fMh OhdI GdefTC hCKQgG Ydi GdSdhc GdTQGFj(B- (3GdYhGed GdeMOOI ddEJLGg fMh OhdI GdefTC(B- (3JUeje GSJQGJjLjGJ GdeRjL GdJShjbj aj Xd GJLGgGJ GdeSJgdcjf fMh OhdI GdefTC(B- (3ebJQMGJ JUeje GdeRjL GdJShjbj ddSdY GdeUQjI(B.s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs